Ameliorative Potential of Tamarindus indica on High Fat Diet Induced Nonalcoholic Fatty Liver Disease in Rats - Suja Rani Sasidharan; Joshua Allan Joseph; Senthilkumar Anandakumar; Vijayabalaji Venkatesan; Chandrasekharan Nair Ariyattu Madhavan; Amit Agarwal (The Scientific World Journal)
Nonalcoholic fatty liver disease (NAFLD), the prevalence of which is rising globally with current upsurge in obesity, is one of the most frequent causes of chronic liver diseases. The present study evaluated the ameliorative effect of extract of Tamarindus indica seed coat (ETS) on high fat diet (HFD) induced NAFLD, after daily administration at 45, 90, and 180 mg/kg body weight dose levels for a period of 6 weeks, in albino Wistar rats. Treatment with ETS at all tested dose levels significantly attenuated the pathological alterations associated with HFD induced NAFLD viz. hepatomegaly, elevated hepatic lipid and lipid peroxides, serum alanine aminotransferase, and free fatty acid levels as well as micro-/macrohepatic steatosis. Moreover, extract treatment markedly reduced body weight and adiposity along with an improvement in insulin resistance index. The study findings, therefore suggested the therapeutic potential of ETS against NAFLD, acting in part through antiobesity, insulin sensitizing, and antioxidant mechanisms.